The genus Deschampsia and the epithet “alpina” - Chiapella, Jorge Oscar; Xue, Zhi-Qing; Greimler, Josef (PhytoKeys)
The epithet “alpina” has been recurrently used in the genus Deschampsia to name plants located in northern regions of Europe, Asia and North America, as a species (Deschampsia alpina (L.) Roem. & Schult.), but also in infraspecific categories (Deschampsia cespitosa subsp. alpina Tzvel. and Deschampsia cespitosa var. alpina Schur.). The morphological and molecular available evidence suggests the existence of a single species, Deschampsia cespitosa (L.) P. Beauv., in which individuals belonging to the same morphological gradient have received different names in different taxonomic categories throughout its wide distribution range. An evaluation of the available names indicates that all uses of the epithet “alpina” are illegitimate. A new combination is proposed at the infraspecific level as Deschampsia cespitosa subsp. neoalpina Chiapella, Xue & Greimler. Fil: Chiapella, Jorge Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigaciones en Biodiversidad y Medioambiente. Universidad Nacional del Comahue. Centro Regional Universidad Bariloche. Instituto de Investigaciones en Biodiversidad y Medioambiente; Argentina Fil: Xue, Zhi-Qing. Universidad de Viena. Instituto de Botanica; Austria Fil: Greimler, Josef. Universidad de Viena. Instituto de Botanica; Austria